Edible insect Locusta migratoria shows intestinal protein digestibility and improves plasma and hepatic lipid metabolism in male rats. (1st December 2022) - Ochiai, Masaru; Tezuka, Kou; Yoshida, Haruka; Akazawa, Takashi; Komiya, Yusuke; Ogasawara, Hideki; Adachi, Yuto; Nakada, Minori
Highlights: Proteins from edible MLP show low amino acid score 63. Proteins from MLP show resistance to gut, but not to small-intestinal digestion. Dietary MLP improves fatty acid profiles related to arteriosclerosis in rats. Dietary MLP suppresses plasma ldl -lipid levels by up-regulating LDL uptake. Dietary MLP suppresses de novo lipogenesis in the liver of rats. Abstract: Although edible insect migratory locusts are considered sustainable food resources with proteins and n-3 lipids, their physiological effects on lipid metabolism are not clarified. Here, we clarified the amino acid (AA) value of the edible migratory locust powder (MLP), protein digestibility, and dietary effects of MLP on growth and lipid metabolism in rats. The AA score was 63, which was low score due to the limiting AA (Trp). MLP protein digestibility was resistant to gut pepsin but digestible to intestinal trypsin and chymotrypsin. Dietary MLP represented favorable growth and enhanced intestinal condition and lipid metabolism in rats, particularly, low-density lipoprotein metabolism and arteriosclerosis-related fatty acid profiles. Liver triglyceride accumulation and fatty acid desaturation indices were increased by activating lipids uptake into the liver, while lipogenic protein expression and enzyme activities and liver function indices were reduced by MLP. Conclusively, intestinal digestible MLP is a nutraceutical for the prevention of dyslipidemia.